2020
DOI: 10.5812/mejrh.99754
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endurance Training with Royal Jelly on CRP Gene Expression in Muscle Tissue of Rats with Alzheimer ’s Disease

Abstract: Background: Studies have shown that Alzheimer's disease (AD) causes neuromuscular dysfunction by damaging different parts of the central nervous system and inflammation that can increase C-reactive protein (CRP) levels. Nevertheless, the beneficial effects of endurance training (ET) and royal jelly (RJ) on inflammation and reduction of CRP are not fully elucidated. Objectives: The aim of this research was to investigate the effect of ET with RJ on gene expression of CRP in muscle tissues of rats with AD. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Royal jelly contains important compounds such as proteins, sugars, lipids, amino acids, vitamins and minerals; It also has a wide range of medicinal functions such as antioxidant, anti-edematous, antimicrobial, anti-allergic and anti-tumor properties and protective effects on immune, inflammatory and nervous systems (21). Nora et al (2020) reported a significant decrease in CRP as a result of eight weeks of endurance training and consumption of royal jelly (100 mg/kg) in the muscle tissue of rats with Alzheimer's disease (22).…”
Section: Discussionmentioning
confidence: 99%
“…Royal jelly contains important compounds such as proteins, sugars, lipids, amino acids, vitamins and minerals; It also has a wide range of medicinal functions such as antioxidant, anti-edematous, antimicrobial, anti-allergic and anti-tumor properties and protective effects on immune, inflammatory and nervous systems (21). Nora et al (2020) reported a significant decrease in CRP as a result of eight weeks of endurance training and consumption of royal jelly (100 mg/kg) in the muscle tissue of rats with Alzheimer's disease (22).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, researchers showed that the use of RJ by cAMP/PKA/CREB/BDNF mechanism inhibits nerve cell apoptosis and reduces DNA damage (17). Although in previous studies, the favorable interactive effects of training and RJ consumption on neurotrophins (15), cognitive function (11), and inflammatory factors (9) have been reported, the exact mechanism of these two in-terventions on the pathways for DNA repair and transcription of metabolism-related genes (ATPase) are not yet fully understood.…”
Section: Introductionmentioning
confidence: 97%
“…Researchers have reported beneficial effects of aerobic exercise on the mental, physical and cognitive health of patients with AD, the intensity, duration of activity, and the most effective duration of exercise, as well as the type of exercise based on differences in contraction and related adaptations, are not yet fully understood (8). In this regard, the results showed that endurance training reduced C-reactive protein in the muscle tissue of AD rats (9). In addition, endurance training on different slopes has been one of the challenges in assessing the type of adaptation in the cognitive function of AD animal models.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Considering the increasing prevalence of cognitive and metabolic disorders in the elderly population, it is important to provide them with effective treatment strategies. Therefore, the positive role of exercise training in improving cognitive function, 5 improving balance and muscle strength, 6 reducing inflammatory factors in skeletal muscle tissue, 7 reducing oxidative stress in cerebral arteries 8 and improving cardiac function has been reported in AD patients. 9 Exercise training with the mechanism of increasing cyclic adenosine monophosphate (cAMP) leads to the phosphorylation of protein kinase A (PKA), and activation of protein kinase activated by cAMP (AMPK) leads to the phosphorylation of PGC1α, increased nuclear transcription, mitochondrial proliferation, recovery of substrate metabolism in skeletal and cardiac muscle, and ultimately weight loss.…”
mentioning
confidence: 99%